Precision medicine: the future of medicine: Medicina de precisión: el futuro de la medicina - Gallo, Aly (2018)
The sequencing of the human genome back in 2001 generated the greatest health knowledgerevolution of the 21st century, thanks to this event today we can clearly know how biologicalsystems work. On the other hand, the implementation of diagnostic platforms increasinglysophisticated and sensitive that added to the development of the pharmaceutical industry, in thelast 18 years, have generated a paradigm shift called: Precision Medicine, a situation that makes itincreasingly distant to think in a medicine such as the one practiced today, based on trial anderror, where the objective is a diagnosis and treatment directed against the symptomatology.In that order of ideas, imagine that at this moment a medical colleague, is treating one of hispatients and to diagnose it has requested a series of support tools such as images or clinicalanalysis, complying with a Clinical Practice Guide that joins his experience will take you (ifnecessary) to design and prescribe a symptomatic and modifying treatment, seeking that thedrugs interact with a specific objective in the biological network underlying the disease, directly orindirectly impacting the progression of the disease and the person; up there all right, to this wecall "conventional therapy", a practice accepted and validated by our health system. DOI: 10.25176/RFMH.v18.n2.1279